Cyberattack Risk Assessment in Electronic banking Technologies (the Case of Software Implementation) - A. A. Berdyugin; P. V. Revenkov (Финансы: теория и практика)
The authors investigate the risks of computer attacks on automated banking systems. The relevance of the study is due to the need to revise the approaches to risk assessment based on the technical components of banking business processes and the consequences of cyber-attacks aimed at banking automated systems in credit institutions. The aim of the study is to describe the developed methods for assessing cyber risks in a commercial bank and provide an option for assessing the risks of information security violations in electronic banking technologies. The methodology of the article includes the analysis of domestic and foreign literature on the research topic, the theoretical and probabilistic method of calculation, computer programming and graphic interpretation of information. The authors analysed the operational risk of a commercial bank to develop components of the operational risk management system in the context of developing electronic banking technologies. They designed a computer program to quantify risk probabilities of cyberattacks on electronic banking technologies (by means of Borland Delphi). The work presents a formalised probabilistic model for determining the most vulnerable segment of risk management techniques used by information security structures. The conclusion is that it is possible to develop a software package based on a mathematical model that reduces the number of checks of risk factors by several times. The research results may be of further use for the development of risk divisions in credit institutions using electronic banking technologies.